Elimination of Misconceptions on English and Motivation - Himpun Panggabean (Bandar Lampung University (UBL), 2013)
The misleading assumptions of Indonesian-speaking learners of English on the nature of English results in psychological burden inhibiting the process of teaching and learning. The assumptions should be eliminated at the beginning of English class. Besides, the instructor should extensively motivate and encourage the learners to maximize their potentials in learning process. Such approach will gradually lead the learners to self-confidence and self-discovery.